Applications of CRISPR/ Cas9 technology in sunflower (helianthus annuus L.) - Uslu, Yağmur Zeynep (My University, 2020)
FAD2-1 enzimi, oleik asidin ayçiçeğindeki linoleik aside dönüşümünü katalize eder. FAD2-1 geni üzerinde yapılan genetik modifikasyonlar oleik ve linoleik yağ asitlerinin kompozisyonlarını değiştirmektedir. CRISPR / Cas9 teknolojisi genom düzenleme için etkili, hızlı ve başarılı bir tekniktir, tarımsal üretkenliği artırmak ve sürdürülebilir tarımsal kalkınmayı hızlandırmak için yeni bir yetiştirme teknolojisi olarak uygulanmaktadır.Bu çalışmada, CRISPR / Cas9 genom düzenleme sisteminin FAD2-1 geninin susturulması ve böylece yüksek oleik ayçiçeği geliştirilmesi amaçlanmıştır. CRISPR / Cas9 aracılı genom düzenlemesi ilk defa ayçiçeği bitkisine uygulanmıştır. Çalışmada iki tane düşük oleik ayçiçeği genotipi kullanılmıştır. FAD2-1 geninin hedefleyen iki adet kılavuz DNA tasarlanmış, kılavuz DNA ekspresyon kasetlerin tek bir reaksiyonla Golden Gate klonlama ile vektöre monte edilmiştir. İki düşük oleik ayçiçeği genotipinin Agrobacterium aracılı transformasyonu ve in vitro çimlenme çalışmaları yapılmıştır. Transforme sürgünlerin seçilimi için kanamisin kullanılmıştır. Ayçiçeğinde letal konsantrasyonu belirlemek için altı farklı konsantrasyonla optimizasyon yapılmıştır. Optimizasyonun sonucu olarak, 100 mg / L kanamisin konsantrasyonu seçilmiştir. Agrobacterium aracılı ayçiçeği transformasyonun zorlukları açıklanmış ve olası çözümler önerilmiştir. Bu çalışma, ayçiçeği yüksek oleik ayçiçeği geliştirmek için CRISPR / Cas9 genom düzenleme sistemi ile değiştirilebileceğini göstermiştir.

Sunflower (Helianthus annuus L.) is the most widespread plant used for production of oil among all oilseeds cultivated in Turkey in terms of agricultural area and production. Sunflower with high oleic acid content is always desirable because of benefits on health and industrial use. The enzyme FAD2-1 catalyzes the conversion of oleic acid to linoleic acid in sunflower. The fatty acid composition can be enhanced by genetic modifications made on FAD2-1 gene. CRISPR/ Cas9 technology provides a useful, quick and effective genome editing and has been applied as a new breeding technique to improve productivity and enhance sustainability in agriculture.In this study, the aim was the applications of CRISPR/ Cas9 genome editing system to knockout FAD2-1 gene resulting in accumulation of oleic acid content. CRISPR/ Cas9 technology was used in sunflower was performed for the first time. Two low oleic sunflower genotypes were used. Two sgRNA driven by which target FAD2-1 gene were designed and sgRNA expression cassettes were assembled into the binary vector by Golden Gate assembly in a single reaction. Agrobacterium-mediated transformation and in vitro germination were studied with two low oleic sunflower genotypes. Putative transformed shoots were selected with kanamycin. Six concentrations of kanamycin were utilized to determine lethal concentration for sunflower. As a result of the optimization, 100 mg/ L kanamycin was chosen to be used. The challenges of Agrobacterium-mediated transformation of sunflower were explained and possible solutions were proposed. This study indicated that sunflower can be modified by CRISPR/ Cas9 genome editing system to develop high oleic sunflower.
Keywords: Agrobacterium aracılı transformasyon Sunflower; Agrobacterium-mediated transformation; Ayçiçeği; Bioengineering; Biyomühendislik; CRISPR/ Cas9; FAD2-1 gene; FAD2-1 geni; Genom düzenleme; Genome editing; Oleic acid; Oleik asit